Implementasi 2D Skeletal Based Animation Engine Menggunakan OpenGL - Mokhamad Zukhruf Mifta Al Firdaus; Eriq Muh. Adams jonema; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In making 2D animation there are several techniques which are quite popular, one of them is skeletal-based animation technique. Skeletal-based animation is a technique where animator only needs parts form character, then adjust the location according to a virtual skeleton, this technique is the same as the animation technique in 3D. But in its development, motion capture or 3D laser scanner technology in making 3D animation have not been used for making 2D animation, especially with skeletal-based animation. And to produce 2D animation needs 50 to 300 animator to draw thousands of characters in different poses with human hands. This causes the animator mostly laborious and time-consuming in making animation. This research focuses on the implementation of 2D skeletal-based animation engine using OpenGL. Animation engine that is implemented using the OpenGL API because OpenGL is a specific API for graphics processing, both 2D and 3D. Also using a Kinect sensor which is one of motion capture technology that no need marker. The result of this research shows the valid result on functionality testing for AnimateFrame and playImportKeyframe component, it shows the animation engine successfully implemented by using OpenGL API and Kinect sensor and can produce animation with skeletal-based animation technique.